2014
DOI: 10.1111/iji.12118
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants of membrane receptors related to recognition and induction of immune response with Helicobacter pylori infection in Ecuadorian individuals

Abstract: Helicobacter pylori (Hp) has a worldwide distribution showing its higher prevalence of infection in developing countries. Toll-like receptors (TLRs) and C-type lectin receptors (CLRs) are proteins that recognize pathogen-associated molecular patterns (PAMPs) and initiate an innate immune response by promoting growth and differentiation of specialized hematopoietic cells for host defense. Gastric infections led by Hp induce a Th-1 cellular immune response, regulated mainly by the expression of IFN-γ. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
2
7
0
3
Order By: Relevance
“…genotype has been reported to be a risk factor for H pylori infection. 37 The present study revealed that the allele frequency G of the IFNGR1-56 site, the allele frequency A at the IFNGR1-600 site, and the allele frequency T of the IFNGR1-565 site were all significantly higher in the recurrence group when compared to the control group. This result showed that IFNGR1 polymorphism may leading to gastric tissue damage.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…genotype has been reported to be a risk factor for H pylori infection. 37 The present study revealed that the allele frequency G of the IFNGR1-56 site, the allele frequency A at the IFNGR1-600 site, and the allele frequency T of the IFNGR1-565 site were all significantly higher in the recurrence group when compared to the control group. This result showed that IFNGR1 polymorphism may leading to gastric tissue damage.…”
Section: Discussionsupporting
confidence: 48%
“…31,34 IFN-γ protects patients from H pylori infection and helps host remove H pylori. 35,36 37 Furthermore, this increases the body's susceptibility to H pylori infection. 40 The IFNGR1-56TT…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el ambiente laboral existen compuestos perjudiciales como son las fibras de asbesto, talco, metales pesados, pesticidas, arsénico, benceno, xileno, tolueno, aminas aromáticas, monoclorhidrato de vinilo, hidrocarburos, radiación ionizante y radiación ultravioleta. Igualmente, existen agentes patógenos asociados al desarrollo del cáncer como son los virus (EBV, VPH, VHB, VHC, VTLH-1 o HHV8), o bacterias como el Helicobacter pylori (Cabrera-Andrade et al, 2014;Paz-y-Miño et al, 2008). El humo del tabaco es uno de los carcinógenos más potentes debido a sus componentes mutágenos como el hidrocarburo aromático policíclico (PAH) y la nitrosamina (Paz-y-Miño et al, 2010;Frank, 2007;Irigaray et al, 2007).…”
Section: Carga Hormonal-unclassified
“…TLR1 is linked to H. pylori-associated gastric lesions (14,15). In a Chinese population, the association between SNPs in the promoter regions of TLR1 rs4833095 and TLR10 rs10004195 and susceptibility to H. pylori infection and precancerous gastric lesions or GC was studied (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%